2006
DOI: 10.1073/pnas.0602447103
|View full text |Cite
|
Sign up to set email alerts
|

Plague dynamics are driven by climate variation

Abstract: The bacterium Yersinia pestis causes bubonic plague. In Central Asia, where human plague is still reported regularly, the bacterium is common in natural populations of great gerbils. By using field data from 1949 -1995 and previously undescribed statistical techniques, we show that Y. pestis prevalence in gerbils increases with warmer springs and wetter summers: A 1°C increase in spring is predicted to lead to a >50% increase in prevalence. Climatic conditions favoring plague apparently existed in this region … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
182
2
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 249 publications
(201 citation statements)
references
References 22 publications
14
182
2
3
Order By: Relevance
“…The optimum model for the rodent-flea-plague system is a multivariate nonlinear model, where the nonlinearity feature pertains to the behavior of the infectious-flea force as a threshold model with the rodent density being a dominant season-specific variable defining the threshold (SI Text). This result suggests that the rodent population 1.5-2 y earlier has to be sufficiently high for an outbreak to occur, which is consistent with but more multifaceted than previous findings (6,14,15).…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…The optimum model for the rodent-flea-plague system is a multivariate nonlinear model, where the nonlinearity feature pertains to the behavior of the infectious-flea force as a threshold model with the rodent density being a dominant season-specific variable defining the threshold (SI Text). This result suggests that the rodent population 1.5-2 y earlier has to be sufficiently high for an outbreak to occur, which is consistent with but more multifaceted than previous findings (6,14,15).…”
Section: Resultssupporting
confidence: 81%
“…We denote the threshold quantity by R eff , the effective reproduction number of the wildlife system. An expression for R 0 is derived in SI Text, and it was earlier derived from a dynamical transmission model by Keeling and Gilligan (16) and applied to data in the work by Stenseth et al (6). It is given by…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In turn, historical records of human infections can only reflect those occasions when Y. pestis spread from its sylvatic environment, and accidentally caused epidemic disease in humans. The dynamics of such occasions is unknown although attempts have been made to associate them with climactic changes [72].…”
Section: Phylogeographic Patterns and Historical Reconstructions Of Pmentioning
confidence: 99%
“…2, 3). Most other studies have reported spring surges in flea populations prior to outbreaks, which corresponds more with the typical annual patterns in flea abundance seen in this study and elsewhere (Anderson and Williams, 1997;Cully et al, 1997;Stenseth et al, 2006). Whatever the cause, it seems likely that the increase in prevalence and abundance of fleas in summer 2004 was a key precursor to plague outbreak in this colony.…”
Section: Discussionmentioning
confidence: 56%